A role for the midbrain reticular formation in delay-based decision making - Jo, Yong Sang; Pyeon, Gyeong Hee; Mizumori, Sheri J. Y. (Frontiers in Systems Neuroscience, 2024)
In many real-life situations, decisions involve temporal delays between actions and their outcomes. During these intervals, waiting is an active process that requires maintaining motivation and anticipating future rewards. This study aimed to explore the role of the midbrain reticular formation (MRF) in delay-based decision-making. We recorded neural activity in the MRF while rats performed delay discounting and reward discrimination tasks, choosing between a smaller, sooner reward and a larger, later reward. Our findings reveal that MRF neurons are integral to maintaining motivation during waiting periods by encoding both the anticipated size and the discounted value of delayed rewards. Furthermore, the inactivation of the MRF led to a significant reduction in the rats’ willingness to wait for delayed rewards. These results demonstrate the MRF’s function in balancing the trade-offs between reward magnitude and timing, providing insight into the neural mechanisms that support sustained motivation and decision-making over time.